Lunar and Martian gravity alter immune cell interactions with endothelia in parabolic flight - Yu Du; Bing Han; Katharina Biere; Nathalie Abdelmalek; Xinyu Shu; Chaoyang Song; Guangyao Chen; Ning Li; Marina Tuschen; Huan Wu; Shujin Sun; Alexander Choukér; et al. (npj Microgravity)
Abstract Returning to the moon and traveling to Mars represent the main targets of human space exploration missions within the upcoming decades. Comparable to microgravity, partial gravity in these destinations is assumed to dysregulate immune functions, thereby threatening astronauts´ health. To investigate the impact of partial gravity on immune cell attachment to vessel endothelia, THP-1 cells and HUVEC cell layers were monitored in a flow chamber system during parabolic flight in lunar (0.16 g) or Martian (0.38 g) gravity. Focus was set on floating speed, cell adhesion, surface molecule expression and cytoskeletal reorganization under basal and TNF-induced inflammatory environment. Floating speed of THP-1 cells was increased in partial gravity, which was accompanied by a successively lower adhesion to the endothelial HUVEC cells. Expression levels of the adhesion markers Mac-1 on THP-1 cells as well as ICAM-1 on HUVECs were found elevated in lunar and Martian gravity, which was aggravated by TNF. Analysis of cytoskeletal organization in HUVECs revealed reduced intracellular F-actin microfilament networks and a stronger cell directionality with stress fiber alignment at cell borders in partial gravity, which was intensified by TNF. In summary, altered immune cell - endothelium interactions as quantified in partial gravity conditions show similarities to cellular behavior in microgravity. However, the different magnitudes of effects in dependence of gravitational level still need to be assessed in further investigations.